The Comparison of the Histological Skin Structures of Common Sunda Toad (Duttaphrynus melanostictus) and Grass Frog (Fejervarya limnocharis) - Lim, Zi Qi; Ahmad Hata, Rasit; Ramlah, Zainudin (UNIMAS Publisher, 2024)
Anuran skin preserves all functional activities, especially for respiration and water regulation. Duttaphrynus melanostictus and Fejervarya limnocharis are the common species found in Borneo lowlands and are well-adapted to humans. Hence, they can reproduce quickly and rapidly in great numbers in the urban area. This study aims to select these urban-type anurans and describe the skin structure and glands. Four regions of skin samples were obtained, namely Dorsal Head (DH), Dorsal Centre (DC), Ventral Head (VH) and Ventral Centre (VC). The microscopic slides were prepared accordingly as in the histological techniques including skin grossing, fixing, processing, embedding, sectioning and were stained with Haematoxylin and Eosin staining. The seromucous glands are most prevalent in all four regions for both species. Parotoid glands are clearly visible in the skin structure of D. melanostictus, while there is a lack of parotoid glands in F. limnocharis. Nonetheless, F. limnocharis contains regular rows of glands, whereas the distribution of glands in D. melanostictus is scattered. In addition, D. melanostictus possess dermal bones, which are absent in F. limnocharis. Since anuran skin is a mucosal surface that in constant direct contact with the environment, their adaptations to harsh habitats should be reflected in the skin, particularly in the urban and invasive species in this study.